Exposure of in vitro maturing pig oocytes to exogenous interleukin-6 is associated with transcriptomic differences in the resulting blastocysts, with enrichment of developmental signaling pathways - Garcia-Canovas, Manuela; Lopez-Jara, Adelina; Parrilla, Inmaculada; Gonzalez-Plaza, Alejandro; Rodriguez-Martinez, Heriberto; Gil, Maria A.; Cuello, Cristina; Martinez, Emilio A. (Frontiers in Veterinary Science, 2026)
IntroductionInterleukin-6 (IL-6) has recently emerged as a promising supplement for in vitro maturation (IVM), enhancing pig blastocyst development and reducing apoptosis following in vitro fertilization (IVF). This study assessed whether IL-6 supplementation during IVM is associated with differences in gene expression in day-7 in vitro-produced blastocysts.MethodsOocytes from prepubertal gilts were matured in IVM medium with (IL-6 IVM group) or without (control group) 100 ng/mL IL-6 and subsequently subjected to IVF. The resulting presumptive zygotes were cultured in vitro for 7 days. Six pools of seven viable blastocysts per group were flash-frozen in liquid nitrogen and stored at −80 °C until microarray analysis. The embryos were analyzed using the GeneChip® Porcine Genome Array (Affymetrix). Differentially expressed genes (DEGs) were identified by ANOVA using a significance threshold of p < 0.01 and a fold change > |1.5|.ResultsCompared to the control, the IL-6 IVM group showed 91 up-regulated and 47 down-regulated DEGs. KEGG analysis of up-regulated genes revealed enrichment in 13 pathways including genes involved in key processes related to lipid metabolism, embryo development, cell proliferation, and immune system. Only two pathways were enriched among down-regulated genes, comprising genes not previously associated with essential roles in embryonic development.DiscussionBlastocysts derived from oocytes matured in vitro with 100 ng/mL of IL-6 exhibited differences in activity in several immune-related and lipid metabolism pathways through the overexpression of specific genes associated with cell proliferation, embryo development, and apoptosis reduction. These findings provide insights consistent with a role of IL-6 during porcine IVM and its association with oocyte developmental competence.